Do volatile compounds produced by Fusarium oxysporum and Verticillium dahliae affect stress tolerance in plants? - Ningxiao Li; Seogchan Kang (Mycology, 2018)
Volatile compounds (VCs) produced by diverse microbes seem to affect plant growth, development and/or stress tolerance. We investigated how VCs released by soilborne fungi Fusarium oxysporum and Verticillium dahliae affect Arabidopsis thaliana responses to abiotic and biotic stresses. Under salt stress, VCs from both fungi helped its growth and increased chlorophyll content. However, in contrast to wild-type A. thaliana (Col-0), V. dahliae VCs failed to increase leaf surface area in auxin signalling mutants aux1-7, tir1-1 and axr1-3. Compared to wild-type Col-0, the degree of lateral root density enhanced by V. dahliae VCs in these mutants was also reduced. Consistent with the involvement of auxin signalling in fungal VC-mediated salt torelance, A. thaliana line carrying DR5::GUS displayed increased auxin accumulation in root apex upon exposure to V. dahliae VCs, and 1-naphthylphthalamic acid, an auxin transport inhibitor, adversely affected V. dahliae VC-mediated salt tolerance. F. oxysporum VCs induced the expression of PR1 but not PDF1.2 in A. thaliana lines containing PR1::GUS and PFD1.2::GUS. When challenged with Pseudomonas syringae after the exposure to F. oxysporum VCs, A. thaliana showed reduced disease symptoms. However, the number of bacterial cells in F. oxysporum VC-treated plants was not significantly different from that in control plants.